Koka ēkas Tallinas ielā 84, Rīgā, iegāde, renovācija un atpūtas centra "Grīziņkalns" izveide - Buliņa, Agija (Latvijas Universitāte, 2020)
Maģistra darba mērķis ir veicināt Grīziņkalna koka arhitektūras attīstību. Grīziņkalna teritorija ir iekļauta Rīgas vēsturiskā centra aizsardzības zonā un koka ēkas tajā ir saglabājušās no 19. gs. sākuma. Koka arhitektūras loma pilsētvides attīstībā un tās izmantošanas iespējas ekonomiskās aktivitātes veicināšanai netiek pietiekami pētītas, tāpēc autore darba ietvaros veica visu Grīziņkalna koka ēku novērtēšanu. Rezultātā tika izvēlēta viena koka ēka un izstrādāts projekts “Koka ēkas Tallinas ielā 84, Rīgā, iegāde, renovācija un atpūtas centra “Grīziņkalns” izveide”.

The aim of the master's thesis is to promote the development of the wooden architecture of Grizinkalns. Grizinkalns is included in the protection zone of the historical centre of Riga and the wooden buildings have preserved in it from the beginning of the 19th century. The role of wooden architecture in the development of urban environment and the opportunities of its exploitation to promote the economic activity have not been sufficiently studied, therefore the author evaluated all the wooden buildings in the area of Grizinkalns. As a result, a single wooden building was selected and the project “The purchase and renovation of the wooden building on 84 Tallinas street, Riga, and the establishment of the recreation center “Grizinkalns”” was developed. Keywords: wooden building, architecture, cultural heritage, Grizinkalns, renovation, urban environment
The purchase and renovation of the wooden building on 84 Tallinas street, Riga, and the establishment of the recreation center "Grizinkalns"
Keywords: Vadībzinātne; Koka ēka; Arhitektūra; Kultūrvēsturiskais mantojums; Grīziņkalns; Renovācija